The Effects of Different Amounts of Thrombin Application on Fat Graft Viability in Rats: An Experimental Study - FİLİNTE, DENİZ (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2019)
Aims: The most important disadvantage of fat graft, which is also a late-term complication, is graft resorption. The aim of this study is to evaluate the effect of thrombin, which is reported to increase the tissue regeneration and angiogenesis in many areas, to viability of fat graft. Settings and Design: Twenty Wistar-Albino type adult male rats were used in the study. 'they were divided into four groups as one control group and three experimental group. Subjects and Methods: Inguinal fat pads were excised and reduced to 500 mg (+/- 1 mg) in all animals. To obtain thrombin, 3 animals were sacrificed. One percent amount of 0.25 mg lidocaine hydrochloride was injected to the scapular regions of the animals. Afterward, subcutaneous cavities were formed there to place the fat tissue inside. After placing the graft, varying proportions of thrombin were injected to the animals in the experimental groups. No thrombin was not injected to the control group. After 90 days, the experimental animals were sacrificed, and the fat grafts were removed. Statistical Analysis Used: The data obtained from control and experimental groups were analyzed using SPSS software (version 20.0; SPSS Inc., Chicago, IL, USA). Normal fat ratio, cyst or vacuole development, inflammation, fibrosis, microvascular density, apoptosis, and weight score differences between groups were compared using Kruskal-Wallis test. To compare two groups with different scores, Mann-Whitney U test was used. The statistical significance level was accepted as 0.05 (P = 0.05). Results: Macroscopic, histological, and statistical evaluations showed that thrombin has reduced the weight and volume loss on fat graft, increased viable fat cell amount and reduced inflammation on receptive area. Conclusion: The positive effects of thrombin on the viability of fat graft have given us courage to use it in further studies. Longer follow-ups are necessary and more studies are required to use it in clinical practice in combination with fat grafts.
Keywords: Autologous tissue transfer; fat grafts; graft viability; thrombin; LONG-TERM SURVIVAL; ADIPOSE-TISSUE; AUTOLOGOUS FAT; TRANSPLANTATION; AUGMENTATION; ANGIOGENESIS; AUTOGRAFTS; RELEASE; PEPTIDE; MUSCLE